The institutional economics of sharing biological information. - Dedeurwaerdere, Tom (International Social Science Journal, 2006)
Within the field of the governance of biodiversity, initiatives for sharing knowledge through networking distributed databases have emerged, operating both on a global scale (such as the Global Biodiversity Information Facility connecting worldwide biodiversity resources in a searchable database portal) and in more focused issue networks (such as the European Human Frozen Tumour Tissue Bank). In this article, I analyse the institutional conditions for the development of these initiatives in the particular case of microbiological resources. Two main results come out of this analysis. First, microbiological information has to be considered as a complex good, having both public good and common pool resources aspects. Second, to solve the incentive problems for this complex good, we have to go beyond a static conception of efficiency (favouring economic incentives through the allocation of intellectual property rights) and adopt a dynamic framework (geared towards the enforcement of norms of cooperation in a context of changing social preferences and processes of knowledge acquisition throughout the entire innovation chain). Building on the methodologies of successful research programmes on dynamic efficiency in other fields of new institutional economics, I discuss a framework for defining a robust set of design rules for the governance of the microbiological commons.